2009
DOI: 10.1186/ar2717
|View full text |Cite
|
Sign up to set email alerts
|

Expression of 5-lipoxygenase and 15-lipoxygenase in rheumatoid arthritis synovium and effects of intraarticular glucocorticoids

Abstract: Introduction It was previously shown that lipoxygenase (LO) pathways are important in the rheumatoid arthritis (RA) inflammatory process and that synovial fluid from RA patients contains high amounts of leukotrienes. We therefore aimed to investigate the 5-LO and 15-LO-1 expression pattern in RA and ostheoarthritis (OA) synovial tissue and to study the effect of intraarticular glucocorticoid (GC) therapy on enzyme expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 56 publications
7
55
0
Order By: Relevance
“…5-lipoxygenase is reported to be present in RA synovium and mostly expressed in macrophages, neutrophils and mast cells in the sublining layer [16]. Here we found that synovial fibroblasts isolated from rheumatoid arthritis patients express high protein levels of 5-LOX which is consistent with high levels of leukotriene B4, a 5-LOX downstream metabolite, found in synovial fluid in rheumatoid arthritis patients [6].…”
Section: Discussionsupporting
confidence: 84%
“…5-lipoxygenase is reported to be present in RA synovium and mostly expressed in macrophages, neutrophils and mast cells in the sublining layer [16]. Here we found that synovial fibroblasts isolated from rheumatoid arthritis patients express high protein levels of 5-LOX which is consistent with high levels of leukotriene B4, a 5-LOX downstream metabolite, found in synovial fluid in rheumatoid arthritis patients [6].…”
Section: Discussionsupporting
confidence: 84%
“…Besides these, other cytokines (IL-1β, IL-6, IL-23), growth factors (TGF-β), inflammatory mediators (signal transducer and activator of transcription (STAT)-3, toll-like receptor (TLR)-2) and genetic factors (coiled-coil alpha-helical rod protein 1 (CCHCR1), steroidogenic acute regulatory protein (StAR), vitamin D receptor (VDR)) significantly accelerate the inflammatory processes in psoriasis (Honma et al 2012;Tiala et al 2007). 15-Lipoxygenase (15-LOX) enzyme in humans is known to be involved in the production of leukotrienes that act as proinflammatory products, giving rise to allergic reactions (Brash et al 1997;Vanderhoek and Bailey 1984), thereby responsible for pathogenesis of many inflammatory disorders, including rheumatoid arthritis, Alzheimer's dementia and psoriasis (Giannopoulos et al 2013;Gheorghe et al 2009). 15-LOX-2 has been implicated in IFN-γ-induced inflammatory processes in psoriatic skin (Setsu et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Tepoxalin, a COX/LOX dual inhibitor, would have unique inflammatory properties as an NSAIDs and directly or indirectly suppress viability of inflammatory synoviocytes by inhibition of LOX. Many reports have shown that 5-LOX plays an important role in various diseases associated with cell proliferation and that inhibition of 5-LOX resulted in cytotoxicity [10,16,31]. Overexpression of 5-LOX in tissue samples of primary tumor, as well as in established cancer cell lines, has been reported [5].…”
Section: Discussionmentioning
confidence: 99%